2003
DOI: 10.1213/01.ane.0000059223.78879.0f
|View full text |Cite
|
Sign up to set email alerts
|

Low Baseline Bispectral Index of the Electroencephalogram in Patients with Dementia

Abstract: This prospective, controlled, observational study demonstrates that electroencephalogram slowing associated with dementia affects the Bispectral Index of the electroencephalogram. A significant proportion of patients with dementia have a lower than normal "awake" Bispectral Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 18 publications
5
40
1
5
Order By: Relevance
“…In agreement with Renna et al [13], we found that the BIS index could predict delirium with a low sensitivity, a high specificity, and an overall good accuracy (Fig. 3).…”
Section: Bis Eegsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with Renna et al [13], we found that the BIS index could predict delirium with a low sensitivity, a high specificity, and an overall good accuracy (Fig. 3).…”
Section: Bis Eegsupporting
confidence: 92%
“…In contrast to the low sensitivity, the specificity of the BIS index was high. Based on these and Renna et al's data [13], the overall accuracy of bilateral BIS as a screening tool for postoperative delirium is similar to conventional, quantitative EEG [29]. We demonstrated that increased plasma cortisol levels are related to postoperative delirium after open-heart surgery, which is in line with previous studies [30,31].…”
Section: Bis Eegsupporting
confidence: 90%
See 2 more Smart Citations
“…In the case of epidural anesthesia, clinical trials have shown that sedation of such patients requires much smaller MAC of Sevoflurane (0.59% compared to 0.92%) to achieve an adequate BIS It is important to note that among patients with dementia value of BIS index (alertness) is lower than in patients who do not have such pathology 31 . Although BIS represents a useful monitoring for the assessment of anesthesia depth, further studies are necessary in patients with congenital disorders of the central nervous system since BIS can give abnormal responses which do not correspond to the specific stage of anesthesia.…”
Section: Monitoring Of Brain Electrical Activitymentioning
confidence: 99%